Extending WiMDA for the data analysis of µ−SR experiments - Gill, GJW; Pratt, FL; Blundell, SJ (IOP Publishing, 2023)
A software extension to the Windows Muon Data Analysis software package WiMDA has been developed for the analysis of µ−SR data, which has been dubbed Negative-WiMDA. In designing Negative-WiMDA, some key features were considered: it should be easily accessed from the main analysis window of WiMDA; it should be able to account for multiple elements in a sample; it should be able to subtract signals treated as unwanted background, allowing the user to focus on a particular element of interest; it should be able to handle transverse-field (TF) data, and perhaps most importantly, it should be intuitive to use. The main features of Negative-WiMDA are presented here with a few examples of their use.